An Analysis of Quantitative Return on Investment of Social Media Marketing Expenditure on Firm Revenue of Small and Medium Enterprises in Pakistan - Piracha, Huma Mushtaq; Karim, Emadul (ACADEMIA International Journal for Social Sciences, 2026)
Although small and medium enterprises (SMEs) in Pakistan are allocating more money to their marketing, the majority of SMEs cannot quantify the monetary benefit they can derive from their social media marketing campaign. The problem that this study focused upon is that there is not any definite attribution system in Pakistan and SMEs may not be guaranteed of the ROIs (Return on Investment) from their social media marketing activities. Since the objective was to explore the relationship between social media marketing spending and revenue generated due to social media marketing of SMEs in Karachi, Lahore, Islamabad, Faisalabad and Peshawar city in Pakistan, the type of research employed in this study was nonexperimental Cross Sectional quantitative research. The theory employed to the investigation contained the theory of return on investment (Brigham & Ehrhardt, 2019) and as well as microeconomic theory (Mankiw, 2020). An adapted, structured online survey based on the (Loveland, 2026) survey was used between January and February 2026, and again between February and April 2026 and 118 surveys were received that could be used. Descriptive Statistics, correlation (Pearson) and Ordinary least square regression method were employed in the methods. Almost three quarters (76%) of the companies surveyed reported having a social media presence, with four in five (80%) stating they have Facebook, 71% reporting having WhatsApp Business, 62% indicating they have Instagram and 29% are using LinkedIn. However, a majority of respondents (65.3%) couldn’t paint a complete picture of the amount of money they invested on social media marketing overall and the sales revenue that came from these investments. When the sample of firms was reduced to those that had full tracking results, an ordinary least squares regression showed a statistically significant positive responsiveness (elasticity) of attributable revenue to social media expense ranging from 0.342 (p = 0.001) when firm size, firm age, and platform and industry mix were controlled for. The conclusion of the study has indicated that the SMEs of Pakistan may get definite monetary benefits at the future, if they invest in social media marketing, but they must develop proper frames for incorporating & assigning the social media marketing analytics with sales analytics.